Efficiency improvement using bis(trifluoromethane) sulfonamide lithium salt as a chemical additive in porphyrin based organic solar cells. Issue 41 (12th October 2016) - Arrechea, Susana; Aljarilla, Ana; de la Cruz, Pilar; Palomares, Emilio; Sharma, Ganesh D.; Langa, Fernando
Abstract : Two new porphyrins with A–π-D–π-A structure show efficiencies up to 7.63% in BHJ solar cells. Abstract : Two new conjugated acceptor–π-donor–π-acceptor (A–π-D–π-A) porphyrins have been synthesised using 3-ethylrhodanine (1a ) or dicyanovinylene (1b ) groups as acceptor units. Their optical and electrochemical properties made these materials excellent electron donors along with PC71 BM as the acceptor for solution-processed bulk heterojunction organic solar cells. The devices based on1a :PC71 BM (1 : 2) and1b :PC71 BM (1 : 2) processed with CB showed low power conversion efficiencies (PCE) of 2.30% and 2.80%, respectively. Nonetheless, after processing the active layer using a mixture of 3 vol% of a pyridine additive in THF, the PCE was enhanced up to 5.14% and 6.06% for1a :PC71 BM and1b :PC71 BM, respectively. Moreover, when we used LiTFSI as the chemical additive in pyridine/CB-processed1b :PC71 BM an excellent PCE of 7.63% was recorded. The effects over the film morphology and the device characteristics ( J sc, V oc and FF) due to the introduction of LiTFSI are discussed.